Knowledge about STD/AIDS and sexual behavior among high school students in Rio de Janeiro, Brazil - Trajman Anete; Belo Márcia Teresa; Teixeira Eleny G.; Dantas Vicente C. S.; Salomão Frederico M.; Cunha Antônio J. Ledo A. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2003)
The incidence of AIDS and other sexually transmitted diseases (STDs) is increasing among adolescents. In order to better understand high-risk sexual behavior among students, a cross-sectional study based on a self-answered anonymous questionnaire was conducted in 10 public and private high schools in Rio de Janeiro, Brazil. Data were obtained on sociodemographics, knowledge of STD/AIDS, and sexual behavior. Among 945 students aged 13-21, 59% were sexually initiated, and the median age at first sexual intercourse was 15 years (range: 7-19). Although 94% reported being aware of the need for condom use for protection, only 34% informed always using condoms during sex. Low family income was associated with unsatisfactory knowledge (OR = 9.40; 95% CI = 6.05-14.60) and inconsistent condom use (OR = 11.60; 95% CI = 5.54-24.30). However, unsatisfactory knowledge was not associated with inconsistent condom use. School-based educational programs should focus on sexual behavior more than on transmission of knowledge, as well as targeting low-income students.